MASYARAKAT HUKUM ADAT DATUK SINARO PUTIH PASANG SURUT KEKUASAAN ADAT DI TENGAH HEGEMONI NEGARA - Ridwan; Isman (Jurnal Niara, 2019)
The Bungo District Government issued Bungo District Regulation No. 9 of 2007 concerning the mention of the Village Chief to Rio, the Village Becomes Dusun and Dusun Being the Kampung has raised several fundamental problems faced by the Indigenous Government of Datuk Sinaro Putih. The problem is the existence of dualism at the level of village institutions, which is caused by the Role of Rio (Village Chief) who is so free to regulate all adat issues in the indigenous law community Datuk Sinaro Putih which has been regulated by Customary Institutions led by Customary Leader. The method used is descriptive qualitative method. Existence of Customary Law Society Datuk Sinaro Putih still exists. Because they were officially recognized by the Bungo District Regulation No. 6 of 2006 concerning Customary Law Society Datuk Sinaro Putih. They still have customary forests as the ancestral heritage of Datuk Sinar Putih. The Hamlet Government has replaced the power of Datuk Sinaro Putih in the field of general government. However, customary power is still held by Datuk Sinaro Putih, including control of customary forest areas. The descendants of Datuk Sinaro Putih make an effort to maintain their existence, including designing Village Regulations on the Customary Law Community Datuk Sinaro Putih and holding annual and five-year events in the form of traditional vows and traditional art performances in the traditional unit of Datuk Sinaro Putih. Keywords: customary law community, Datuk Sinaro Putih, customary power, state hegemony